Women's health and nutrition role of state and voluntary organizations - Verma, Arpita (Jaipur Rawat Publications, 2017)
Women's Health and Nutrition critically addresses women's health and nutritional status in the rural areas of India. In general, an Indian woman experiences a lower nutritional status than the men in the society because of various social and cultural factors. The objective behind the book is to understand and analyze the health and nutritional status of rural women in the villages of Uttar Pradesh. A unique aspect of the book is its analysis of the nutritional requirement of rural women in terms of calorie consumption and impact of social factors in their health and nutritional status. The book covers general profile of studied villages, nutritional status of married women, general diseases, reproductive health, utilization of maternal and child health, family planning services and awareness of HIV/AIDS among women, state and NGOs interventions, state level programs and schemes related to women's health and nutrition, and their achievements. The intent of this book is to help readers to acquaint themselves with the ground reality and status of the health of women living in India's rural areas. It frames policies while focusing on schemes which shall be in the best interest of both the society, as well as the government. [Subject: Gender Studies, Health Studies, Nutrition Studies, Social Work]
Keywords: Rural women -- Health and hygiene; Voluntary health agencies; Women -- Nutrition -- Requirements; Women's health service; India -- Bara Banki